LEGITIMACY OF HADITH AMAR MAKRUF NAHI MUNKAR AS EVIDENCE OF VIOLENCE BY FPI - Hamid, Idham; Awwaliyah, Neny Muthiatul (State Islamic University of Datokarama Palu, 2021)
This paper explains the concept that was initiated by the Islamic Defenders Front (FPI) mass organization in applying amar makruf nahi munkar. The concept is based on the Prophet's hadith. which was narrated from Abu Said al-Khudri about the steps taken when looking at the munkar that occurred in the community. The facts on the ground show that, the steps taken by FPI when eradicating the impression are only following the first editorial on the hadith, namely preventing it with a 'hand' which is often interpreted as an act of violence. So it is not uncommon when conducting executions in the field often causes conflicts that trigger hostilities to the point of conflict with criminal law. This is the result of textual understanding and partial impression in understanding the hadith amar makruf nahi munkar. The offer to understand the verses contextually and review aspects of their maqasyid is a necessity when they want to apply them to the social spaces of Indonesia that are diverse in the various religions and cultures of their people and are bound by kuhap (legal and criminal laws). Thus, ignoring the context of the universality of the traditions will only lead to greater harm, on the contrary by prioritizing moral ideals in the traditions, it will be easily actualized in the contemporary context without colliding with law and culture.